Variation in Output Shares and Endogenous Matching in Land Rental Contracts - Desta Brhanu; Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2018)
We investigate the extent of variation in output sharing in land rental contracts and alternative hypotheses to explain this variation. Close to half of the rental contracts in our study in northern Ethiopia have output shares that deviate from the dominant 50-50 equal sharing. Variation in land quality, the relative bargaining power of landlords and tenants, production risks and shocks are hypothesized to influence output shares. Matched data of landlords and tenants are used. The importance of endogenous matching of landlords and tenants is investigated by assessing how endogenous tenant characteristics are correlated with landlord characteristics. We find evidence of negative assortative matching for key resource characteristics. A control function approach is used to control for endogenous matching in the output share models. The results reveal that production risks as well as relative bargaining power affect output shares in the reverse tenancy setting with tenants being relatively wealthier and influential than landlords.
Keywords: Q15; 330; Land rental contracts; sharecropping; output shares; endogenous matching; control function approach